Kirsten Sand. Arkitekt for sin tid - Seip, Elisabeth (Nordlit, 2015)
Towards the end of World War II the retreating Germans burnt down nearly all buildings and other constructions in the counties of Finnmark and the northern parts of Troms in North Norway. The population evacuated but many returned as soon as possible, only to find themselves homeless. At this very demanding point Kirsten Sand decided to travel north, and do whatever she could as an architect to help. The pre-war housing situation was generally difficult. Low building standards and lack of money forced families in the cities to live under bad conditions. Kirsten Sand studied these conditions and took part in the efforts to better the situation. This knowledge provided a good starting point for the work she undertook after the war, in particular her profound understanding of the situation of women, their working conditions and positions in the household and society. Houses designed by Sand and her helpmates are simple but adequate, taking into account these women’s point of view. Ingebjørg Hage has thrown light on the work of Kirsten Sand in Finnmark and Troms in several ways. This article aims at describing Sand’s background as an architect before she left Oslo to travel north. It describes how housing and housing policy since long had been central to architects, especially so within the group she belonged to. In pre-war Oslo she had been engaged in planning and designing hospitals. During a period as inspector for the health authorities she learned a lot about the living conditions of people in general. After establishing her own architect’s office she mostly designed family houses, and during the war she engaged in research that further deepened her knowledge in the field. Thus she was particularly well equipped for the demanding tasks she undertook in the summer of 1945.